Awareness and Readiness on Pregnancy Attending Antenatal Care - Acosta, Bernadette G.; Alicaya, Kate Nathalie E.; Atang, Rica Loraine D.; Balagtas, Hannah Alaine D.R.; Barlis, Khurt Ian M.; Bautista, Kim Aliah A.; Gamiao, Kristhine Abegail M. (Proceedings Series on Health & Medical Sciences, 2025)
This study emphasizes the importance of engaging pregnant women in antenatal care to improve maternal and child health outcomes. It seeks to investigate these aspects in detail, providing insightful information that can be applied to creating initiatives to improve antenatal care use. The research was conducted using survey questionnaires via purposive sampling method for 400 pregnant women aged 15-49 attending antenatal care in Cabanatuan City. The study investigated the level of awareness and readiness among pregnant women regarding antenatal care, evaluating their readiness to participate actively in essential care using quantitative descriptive research. This study shows participants' awareness levels regarding pregnancy-related issues such as prenatal nutrition, maternal health screenings, and birth preparedness. The population of this study was the pregnant women from the municipality of Cabanatuan City, Nueva Ecija. The inclusion criteria for this study are pregnant women aged 15-49 years old, and the exclusion criteria for this study are pregnant women aged 15 years old and below and 49 years old and above who are attending antenatal care in Cabanatuan City, Nueva Ecija. Additionally, readiness measures exhibited a span of responses, highlighting women's emotional preparedness for the challenges ahead.The research findings explore pregnant women's socio- demographic profile, awareness, and readiness in Cabanatuan City. Most respondents are aged 26-30, have a high school level education, are married, and earn a monthly income of 15,000 or below and most have had one pregnancy. Awareness regarding pregnancy standards is moderate, with a high awareness of avoiding self-aware conditions and good knowledge about pregnancy. Pregnant women exhibit motivation and readiness for pregnancy, prioritizing their baby's health and seeking support from partners and family.